School Climate and Self-Esteem of Secondary School Students (International Journal of Food and Nutritional Sciences, 2022)
The present study attempts to assess the school climate and self-esteem of secondary school students of Kashmir. This study was conducted on a sample of 600 secondary students, studying at both government and private secondary level schools of Kashmir. To assess the school climate of secondary schools, the investigator has used school climate scale developed by S.P Singh and Imam (2015). To study the self-esteem of secondary school students, Coppersmith self-esteem inventory was used. The findings of the study revealed that there is a significant difference between government and private secondary schools on perceived school climate. There is also a significant difference between government and private secondary school students on self-esteem. The findings of the study also reflected that there is a significant positive relationship between self-esteem and school climate.